The Effect of Biofertilizer Application and Storage Period of Bulb on the Growth and Yield of Shallot Cultivar Bima - Nuryadin, Acep Khatin; Nugraha, Nunu Indra; Budirokhman, Dodi; Trisnaningsih, Umi (Migration Letters, 2024)
The shallot (Allium Ascalonicum L) is one of the leading horticultural commodities that has high economic value. Efforts to increase shallot yields are carried out by providing fertilizer and treating seeds. This research aimed to determine the interaction between the effect of Liquid Organic Biofertilizer (LOB) concentration and the bulb storage period on the growth and yield of shallot. The research was conducted in Baros Village, Kejiwaan District, Brebes Regency with a period of June–August 2023. The experimental design used was a randomized complete block design with a factorial pattern. The treatment consisted of two factors, namely LOB concentration (0, 4, 8, and 12 ml /L) and bulb storage periods (1, 2, and 3 months), and all treatments were repeated three times. The variables observed were plant height, number of tillers, number of leaves, root volume, number of bulbs, bulb diameter, fresh weight of bulbs per cluster, fresh weight of bulbs per plot, dry weight of bulbs per cluster, and dry weight of bulbs per plot. The results showed that there was a significant interaction between the effect of LOB concentration and the bulb storage period on the number of leaves at 21 DAP, 28 DAP, 35 DAP, root volume at 45 DAP, and 60 DAP, plant growth rate at 30-45 DAP, number of bulbs per plant, bulb diameter, fresh bulb weight per cluster, fresh bulb weight per plot, dry bulb weight per cluster and dry bulb weight per plot. LOB treatment of 8 ml/L and bulb storage period of 3 months gave the best results, namely 5.24 kg/plot of dry bulbs.